Seeker beware: The interpersonal costs of ignoring advice - Blunden, Hayley; Logg, Jennifer M.; Brooks, Alison Wood; John, Leslie K.; Gino, Francesca (Organizational behavior and human decision processes, 2019)
•Advisors interpersonally penalize those who do not follow their advice.•Expert advisors penalize seekers more than non-expert advisors.•Advisors interpersonally penalize seekers consulting multiple advisors.•Advisors to “multiple advice-seekers” perceive their advice will be disregarded.•Advice seekers view the purpose of seeking advice as gathering information.•Advisors (vs. seekers) view their purpose as more to provide direction.•Seekers should consider interpersonal goals alongside decision accuracy ones. Prior advice research has focused on why people rely on (or ignore) advice and its impact on judgment accuracy. We expand the consideration of advice-seeking outcomes by investigating the interpersonal consequences of advice seekers’ decisions. Across nine studies, we show that advisors interpersonally penalize seekers who disregard their advice, and that these reactions are especially strong among expert advisors. This penalty also drives advisor reactions to a widely-recommended advice-seeking strategy: soliciting multiple advisors to leverage the wisdom of crowds. Advisors denigrate and distance themselves from seekers who they learn consulted others, an effect mediated by perceptions that their own advice will be disregarded. Underlying these effects is an asymmetry between advisors’ and seekers’ beliefs about the purpose of the advice exchange: whereas advisors believe giving advice is more about narrowing the option set by providing direction, seekers believe soliciting advice is more about widening the option set by gathering information.